Molecular Epidemiology of Hepatitis D Virus in the North-East Region of Romania - Laura Iulia Grecu; Mariana Pavel-Tanasa; Lilia Matei; Camelia Sultana; Simona Maria Ruta; Razvan Ioan Grecu; Ramona Gabriela Ursu; Petru Cianga; Luminita Smaranda Iancu (Pathogens)
The hepatitis D virus (HDV) superinfection of individuals with chronic hepatitis B virus (HBV) infection causes severe liver damage and the poorest long-term prognosis among viral hepatitis. This is attributed to the unique pathogenic mechanisms of HDV characterized by a direct cytopathic effect on hepatocytes and a significant impairment of the host immune response. The HDV genotype largely influences the extent of the pathogenic mechanisms with consequences on disease progression towards cirrhosis, liver decompensation, or hepatocellular carcinoma. In this context, identifying the circulating HDV genotypes in European regions with high prevalence, such as Romania, is crucial for effectively managing the long-term liver health. Here, we report the first comprehensive HDV study in Romania that clinically characterizes 82 patients and performs HDV genotyping by combining the nested-PCR reaction with sequencing analysis in 49 samples with an HDV-RNA load higher than 5000 IU/mL. While all isolates in our study belong to the HDV-1 genotype, the phylogenetic analysis based on sequence data from GenBank reveals the presence of the following potential three groups: (i) Italy and France; (ii) Spain; and (iii) Turkey, Iran, Pakistan, and Germany. This broad clustering highlights the recent surge in migration to and from Western Europe and the Middle East. Equally important, no differences in viral markers, clinical and paraclinical parameters, or treatment options were observed between these identified clusters. Nevertheless, this study considerably advances the understanding of hepatitis D epidemiology and clinical aspects in Romania.